Gender identity disorder is not simply two in one - Ali, Syed Masroor; Khan, Abdul Ghani (The Faculty of Medicine, International Islamic University Malaysia, 2013)
A Case Report on Gender Identity Disorder with Recurrent Depressive Disorder is presented. Individuals having this disorder often exhibit discomfort about their actual anatomic gender, and they may have wished to alter their bodies. Sex role-stereotypes adopted during childhood are the beliefs, characteristics and behaviors of individual cultures that are considered normal and appropriate for boys and girls to possess. These "norms" are influenced by one's family and friends, the mass-media, and their community. Since some cultures disapprove of cross-gender behavior, it often results in significant problems for affected individuals and those in close relationships with them. The importance of treatment is not only because of the high rate of mental-health problems, including Depression but with higher suicide rate among untreated transsexual people than in the general population. These problems are not usually related to the gender identity issues themselves, but the social and cultural responses to gender-deviated individuals. An example which classically illustrates Gender Identity Disorder is the case of a young man from Brunei Darussalam, who was seen and treated. This contribution will highlight the cultural and religious perspective of this Disorder.